PENGARUH KONSUMSI AIR KELAPA MUDA DAN BIJI CHIA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS BUKIT SANGKAL - Yora Nopriani; Tarissa Amanda (LPPM STIKes Mitra Adiguna, 2026)
Hypertension, often referred to as The Silent Killer, is a deadly disease that lacks symptoms to warn its victims. If hypertension is not managed, various causes will arise, including disease complications such as heart attacks, strokes, kidney failure, and even death. Therefore, it is necessary to manage hypertension, which can be done through two approaches: pharmacological and non-pharmacological. Pharmacological therapy uses medications within certain limits that can have negative effects on the human body if used for a long time. Whereas non pharmacological therapy is therapy without the use of drugs, such as modifying lifestyle, maintaining a balanced diet, eating fruits and vegetables, and also consuming young coconut water and chia seeds to lower blood pressure. The aim of this study is to determine the effect of consuming young coconut water and chia seeds on lowering blood pressure in the elderly with hypertension in the working area of Bukit Sangkal Health Center in 2024. The research method uses a pre experimental design with a one group pre-post test design. The sample of this study consisted of 32 elderly individuals with high blood pressure. The results obtained show an influence on blood pressure before and after the administration of young coconut water and chia seeds, where the mean systolic blood pressure was 168.91 and after was 148.84, and the mean diastolic blood pressure was 97.44 and after was 82.44. Advice for healthcare workers is to use the results of this study as input and a source of information when counseling hypertension patients, especially the elderly, to use non-pharmacological therapy to lower high blood pressure, by regularly consuming young coconut water and chia seeds, which contain potassium that can stabilize blood pressure.